2020
DOI: 10.1007/s12070-020-01878-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Budesonide Nasal Irrigation After Endoscopic Sinus Surgery in Chronic Allergic Rhinosinusitis with Polyps

Abstract: Nasal polyposis is one of the most common chronic upper airway diseases. Management of allergic rhinosinusitis with polyps is to control the disease process and the local immune response of the nasal mucosa. This is achieved by surgical removal of polypoid mucosa of all sinuses by functional endoscopic sinus surgery (FESS) followed by suppression of local immune response by using steroids. Budesonide nasal douching was introduced recently for postoperative management of patients with allergic rhinosinusitis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Budesonide is a powerful anti-inflammatory and anti-allergic drug. After topical administration, it is beneficial to inhibit the activation of various inflammatory cells in the nasal cavity, reduce inflammatory damage in the lesion, and promote the absorption of mucosal edema, so as to accelerate the recovery of nasal function and relieve symptoms such as nasal congestion and purulent tears [ 10 ]. However, there are relatively few studies on the comprehensive efficacy of endoscopic sinus surgery combined with budesonide treatment in patients with sinusitis.…”
Section: Introductionmentioning
confidence: 99%
“…Budesonide is a powerful anti-inflammatory and anti-allergic drug. After topical administration, it is beneficial to inhibit the activation of various inflammatory cells in the nasal cavity, reduce inflammatory damage in the lesion, and promote the absorption of mucosal edema, so as to accelerate the recovery of nasal function and relieve symptoms such as nasal congestion and purulent tears [ 10 ]. However, there are relatively few studies on the comprehensive efficacy of endoscopic sinus surgery combined with budesonide treatment in patients with sinusitis.…”
Section: Introductionmentioning
confidence: 99%
“…Budesonide nasal irrigation has been found to be better that saline irrigation, with lesser mucosal oedema, secretions and scarring and lower incidence of postoperative polypoidal changes [ 27 , 28 ]. In a randomized double-blinded placebo-controlled trial in post sinus surgery patients, the corticosteroid nasal irrigation had greater improvement on nasal blockage, a greater improvement on Lund- Mackay score and less inflammation on modified Lund-Mackay score at 12 months compared to steroid nasal sprays [ 29 ].…”
Section: Sino-nasal Irrigationmentioning
confidence: 99%
“…Postoperatively, patients continue maintenance topical therapies. Historically, steroid sprays have been used, although recent studies have shown that high‐volume steroid irrigations are more effective 3–5 . Numerous studies have demonstrated the safety of longitudinal intranasal use of various steroid irrigations 6 …”
Section: Introductionmentioning
confidence: 99%
“…Historically, steroid sprays have been used, although recent studies have shown that high-volume steroid irrigations are more effective. [3][4][5] Numerous studies have demonstrated the safety of longitudinal intranasal use of various steroid irrigations. 6 This is the first study to assess the effect of doseescalated intranasal mometasone irrigations on disease burden and patient-reported sinonasal symptoms following surgery.…”
Section: Introductionmentioning
confidence: 99%